2012
DOI: 10.2165/11633220-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Treatments for Vertebral Compression Fractures

Abstract: Among patients for whom surgical treatment was indicated, kyphoplasty was found to be cost effective, and perhaps even cost saving, compared with vertebroplasty. Even for the oldest patients (85 years of age and older), both interventions would be considered cost effective in terms of cost per life-year gained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…26 Cumulative evidence demonstrates that kyphoplasty and vertebroplasty provide better outcome than nonsurgical management in RCTs and meta-analyses 4,5,7,[9][10][11]27,28 and acceptable cost-effectiveness ratios. 11,[29][30][31] Several large retrospective studies using claims data, investigating BKP, VP, and nonsurgical management, provide additional evidence. [32][33][34][35] Although 2 blinded RCTs concluded that vertebroplasty was similar to a local anesthetic "sham" intervention, 36,37 these trials have several important limitations, including atypically broad inclusion criteria, allowance of chronic fractures, small sample size, and, in 1 study, high crossover, all of which preclude definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…26 Cumulative evidence demonstrates that kyphoplasty and vertebroplasty provide better outcome than nonsurgical management in RCTs and meta-analyses 4,5,7,[9][10][11]27,28 and acceptable cost-effectiveness ratios. 11,[29][30][31] Several large retrospective studies using claims data, investigating BKP, VP, and nonsurgical management, provide additional evidence. [32][33][34][35] Although 2 blinded RCTs concluded that vertebroplasty was similar to a local anesthetic "sham" intervention, 36,37 these trials have several important limitations, including atypically broad inclusion criteria, allowance of chronic fractures, small sample size, and, in 1 study, high crossover, all of which preclude definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Within the current literature we have found several randomized clinical trials comparing either kyphoplasty or vertebroplasty to nonsurgical management (NSM),2–4,6,31–34 and several reports that compare the cost-effectiveness of these procedures compared with NSM 4,29,35–37. Thus, mounting evidence document the benefits of kyphoplasty and vertebroplasty over standard NSM.…”
Section: Discussionmentioning
confidence: 99%
“…Ong et al 19 found that, despite higher initial treatment costs of kyphoplasty, vertebroplasty was less cost-effective due to increased utilization of medical resources (partly due to retreatment) in the postoperative period over the 2 years after surgery. Edidin et al 20 found that kyphoplasty was cost-effective—and perhaps even cost-saving—compared with vertebroplasty using Medicare claims data. Again, these cost-effectiveness analysis studies are from non-randomized populations and are subject to significant selection bias.…”
Section: Discussionmentioning
confidence: 99%